Academic research – a catalyst for the innovation process within companies in Romania - Rodica Pamfilie; Smaranda Giuşcă; Robert Bumbac (Amfiteatru Economic)
Current economic developments make the use of scientific resources, especially academic research, to be no longer just an option for companies wanting to remain competitive, but a necessity. This statement is based on the research conducted by the authors during the last three years on the companies` performance in Romania regarding the results of the innovation process and capitalization on scientific resources in order to improve this vital process. To achieve this, a mechanism should be created, through which key players in the market - companies, universities, research institutes and government - could work together towards the common goal of economic growth. This mechanism would help companies move beyond incremental innovation by using knowledge generated by universities or research institutes. This can be achieved with the support of the governmental environment, by adopting policies and creating a general favourable climate for research and by fostering its integration among companies. This paper presents an analysis of the degree to which companies in Romania use the results of academic research when developing new products or services. Among the identified issues we include the Romanian companies’ tendency to perform individual research and development projects, though their frequency is quite low given the difficulties in successfully delivering them to the market. The research shows the importance of using academic research when moving beyond incremental improvements and developing the innovation processes within the company. The prospect of a future model of the university as a knowledge and innovation hub of can significantly contribute to the capitalization of academic research by companies in order to develop sustainable businesses.